Action of decoquinate in altering feed efficiency of ruminants - Harmon, D.L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
The effects of adding decoquinate (Deccox®) to the diet at 0, 0.5, or 5 mg per kg body weight were evaluated with diets of 30 and 80% concentrate. Decoquinate did not influence rumen or plasma metabolites, diet digestibility, or volatile fatty acid production. No metabolic effects were seen that would suggest a role for decoquinate in altering rumen fermentation and feed efficiency of ruminants.
Keywords: Beef; Feed efficiency; Decoquinate; Digestibility; Fermentation